The Structure of Plutarch's Adversus Colotem - Kechagia, E (Oxford University Press, 2011)
This chapter focuses on the structure of the Adversus Colotem and examines the reasoning underlying the order of exposition which Plutarch followed in his response to Colotes' book. It argues that Plutarch arranged his material thematically following the ancient tripartite division of philosophy. This enabled him firstly to criticise not only Colotes' particular claims against the philosophers but main aspects of all three branches of Epicurean philosophy (physics, canonic, ethics); and secondly to give an outline of some of the most important theories in the history of Greek philosophy to Colotes' day.